Language Barrier: Theory of Truth in Intercultural EFL - Jayanti, Lukitaning Nur (English Department, Faculty of Humanities, Andalas University, 2024)
This paper elaborates the explanation of an incorrect and misconceptionunderstanding of meaning in teaching English as a foreign language inIndonesia. This research is conducted with a discussion consisting of logicalreasoning about the detailed explanation as a method to deal with the issue.It was done by cross-checking and reviewing eclectically from dissimilarsources in the related field of study as well. Moreover, the discussion andresult are affirmed and evaluated by utilizing the relevant existing studiesand research. The scoop and limitation in this study are that the subject isreferring to the Indonesian students that learn the English language as aforeign language in formal education school.The study found that this phenomenon is happening because of thepedagogical need based on the standard formal education school curriculumin Indonesia that focusing English as a communication language rather thananything else. A teacher neither needs nor bother to explain the languagein a deeper sense of meaning and only teaches what is necessary for thestudent requirement. This makes the English language used in Indonesianschools lose its true meaning and understanding because of the differencein intercultural understanding. This mostly happens in a school that useslocalized English that has been adapted in our culture and habits as foreignspeakers. Hence some vocabularies and phrases end up being simplified toreduce teacher time effort to explain further about language meaning andtruth.